Reinterpreting Coercive Begging in Islam through the Tafsir of Wahbah al-Zuḥaili - Anam, A'azliansyah Farizil; Maram, Ahmad Nabilul; Nafiah, Zahrah Faizatun; Hidayat, Hakmi (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2025)
The phenomenon of coercive begging raises complex social and ethical challenges. As a contemporary mufassir, Wahbah al-Zuḥaili addresses this issue through a distinctive approach that integrates modern social-ethical perspectives with Qur’anic teachings, specifically in QS. al-Baqarah (2): 273. This study aims to assess the ongoing relevance of his interpretation. It focuses on how al-Zuḥaili interprets coercive begging in this verse, as well as the epistemological and socio-political factors that shape his perspective. Employing Gadamer’s hermeneutics as the analytical framework, this research bridges the horizon of classical texts with contemporary social realities. The findings demonstrate that al-Zuḥaili’s interpretive method is both dynamic and integrative: he draws on lexical and grammatical analysis, classical and modern textual engagement, and historical experience to construct contextual and meaningful interpretations, all while remaining faithful to the core of the divine message. This model contributes to the evolution of Qur’anic interpretation, making it more responsive to the needs of contemporary society. The study reveals that al-Zuḥaili interprets the phrase lā yasʾalūn al-nās ilḥāfā as a prohibition of coercion rather than a blanket prohibition of asking. This interpretation reflects his engagement with the realities of coercive begging in Syria and Egypt during his lifetime. Al-Zuḥaili responds to the tension between scriptural text and contemporary socio-legal realities by proposing a practical alternative: rather than relying solely on criminal sanctions, governments should systematically identify vulnerable groups, foster interactive dialogue, and strengthen social welfare programs.